2008
DOI: 10.1088/1751-8113/41/49/495201
|View full text |Cite
|
Sign up to set email alerts
|

Exact accelerating solitons in nonholonomic deformation of the KdV equation with a two-fold integrable hierarchy

Abstract: Recently proposed nonholonomic deformation of the KdV equation is solved through inverse scattering method by constructing AKNS type Lax pair. Exact N-soliton solutions are found for the basic field and the deforming function showing unusual ac(de)celerated motion. Two-fold integrable hierarchy is revealed, one with usual higher order dispersion and the other with novel higher nonholonomic deformations.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
65
0
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(73 citation statements)
references
References 9 publications
3
65
0
5
Order By: Relevance
“…On the other hand, in addition to the well-known Camassa-Holms and Degasperis-Procesi equations, some other unusual new integrable equations were recently discovered, namely, the KdV6 [4], LF DNLS [5], mKdV-SG [10], and higher mKdV [11] equations. We realized that these uncommon equations are merely particular cases of general integrable perturbations of the AKNS-Zakharov-Shabat and the KN systems [6]- [8].…”
Section: Integrable Perturbation Through Nonholonomic Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, in addition to the well-known Camassa-Holms and Degasperis-Procesi equations, some other unusual new integrable equations were recently discovered, namely, the KdV6 [4], LF DNLS [5], mKdV-SG [10], and higher mKdV [11] equations. We realized that these uncommon equations are merely particular cases of general integrable perturbations of the AKNS-Zakharov-Shabat and the KN systems [6]- [8].…”
Section: Integrable Perturbation Through Nonholonomic Deformationmentioning
confidence: 99%
“…One such area is the nonholonomic deformation of integrable systems [2], which leads to integrable perturbations of known integrable systems with a twofold hierarchy and rich soliton dynamics [3] and also to discovering new equations such as integrable perturbations of the KdV (mKdV), sine-Gordon (SG), nonlinear Schrödinger (NLS), and the derivative NLS (DNLS) equations, and to obtaining some recently proposed equations, for example, the KdV6 [4] and Lennels-Fokas (LF) [5] equations, and so on. Moreover, using nonholomorphic deformations allows explaining the integrability of these systems and obtaining exact soliton solutions [3], [6]- [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kundu has shown that Eq. (1.4) admits a Lax pair [9]. Also Kupershmidt [8] has demonstrated that Eq.…”
Section: Introductionmentioning
confidence: 97%
“…Equations (1.3) known as KdV 6 in the literature and can also be written as u t − u xxx − 6uu x = g x (t, x), (1.4a) g xxx + 4ug x + 2u x g = 0, (1.4b) which can be viewed as a nonholonomic deformation of the Korteweg-deVries equation [9,11]. It is appropriate to mention that Eq.…”
Section: Introductionmentioning
confidence: 99%